Fatores críticos de sucesso do lean healthcare: uma aplicação prática em uma unidade hospitalar localizada na cidade de Cachoeira do Sul - Klering, Monaliza (2021)
Lean is a management philosophy derived from the Toyota System, widely applied in industry and adapted to the healthcare area with the objective of reducing costs and optimizing resources through a review of processes to generate value for the patient. Lean Healthcare is the Lean Manufacturing philosophy applied in the healthcare area. Lean Healthcare aims to create and provide maximum added value, its application expects to consume fewer resources, reduce waste and also leverage the knowledge and skills of employees involved in the process. This philosophy has been used in several sectors, with health services being the most sought after. This work aims to evaluate critical success factors for the implementation of Lean Healthcare in a hospital unit. To accomplish the objective, the AHP method was used. The Analytic Hierarchy Process (AHP) is a method to help people make complex decisions. More than just determining the right decision, AHP helps people choose and justify their choice. Some results can be highlighted. Among the groups, the categories Management and Leadership and Processes were highlighted by the participants. Among the subcategories with the greatest weight of relevance, it is important to highlight the patients subcategory, since a hospital unit aims to provide the best care possible for the patient. A limitation of the study is that it was applied in only one hospital unit, as a future work it is intended to apply it in more units and, therefore, carry out a comparison of its results.